'Most importantly, I hope God keeps illness away from us': The context and challenges surrounding access to health care for Syrian refugees in Lebanon. Issue 11 (1st November 2020) - Sousa, Cindy; Akesson, Bree; Badawi, Dena
ABSTRACT: The influx of 1.5 million Syrians into Lebanon has created an increased demand for health services, which is largely unmet, due to cost, a highly fragmented and privatised system, and crises around legal documentation and refugee status. The aim of this study was to use a constant comparison analysis of qualitative data to explore how Syrian refugees living in Lebanon describe their experiences accessing healthcare ( N  = 351 individuals within 46 families). Pervasive fear, lack of confidence in the medical system, and high costs all hinder access to healthcare for Syrians in Lebanon. Findings demonstrate the need for attention to the costs and accessibility of care, and for stronger coordination of care within a centrally led comprehensive emergency plan. While we attend to understanding and alleviating the barriers surrounding refugee healthcare, we must also address the underlying cause of health crisis: the brutal realities caused by armed conflict.